High-Temperature Chemical Stability of Cr(III) Oxide Refractories in the Presence of Calcium Aluminate Cement - Tengteng Xu (MDPI AG, 2021)
Al2O3-CaO-Cr2O3 castables are used in various furnaces due to excellent corrosion resistance and sufficient early strength, but toxic Cr(VI) generation during service remains a concern. Here, we investigated the relative reactivity of analogous Cr(III) phases such as Cr2O3, (Al1−xCrx)2O3 and in situ Cr(III) solid solution with the calcium aluminate cement under an oxidizing atmosphere at various temperatures. The aim is to comprehend the relative Cr(VI) generation in the low-cement castables (Al2O3-CaO-Cr2O3-O2 system) and achieve an environment-friendly application. The solid-state reactions and Cr(VI) formation were investigated using powder XRD, SEM, and leaching tests. Compared to Cr2O3, the stability of (Al1−xCrx)2O3 against CAC was much higher, which improved gradually with the concentration of Al2O3 in (Al1−xCrx)2O3. The substitution of Cr2O3 with (Al1−xCrx)2O3 in the Al2O3-CaO-Cr2O3 castables could completely inhibit the formation of Cr(VI) compound CaCrO4 at 500–1100 °C and could drastically suppress Ca4Al6CrO16 generation at 900 to 1300 °C. The Cr(VI) reduction amounting up to 98.1% could be achieved by replacing Cr2O3 with (Al1−xCrx)2O3 solid solution. However, in situ stabilized Cr(III) phases as a mixture of (Al1−xCrx)2O3 and Ca(Al12−xCrx)O19 solid solution hardly reveal any reoxidation. Moreover, the CA6 was much more stable than CA and CA2, and it did not participate in any chemical reaction with (Al1−xCrx)2O3 solid solution.